2010
DOI: 10.1007/978-3-642-11598-1_11
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Roll Type Incremental Micro Pattern Imprint System for Large Area Pattern Replication

Abstract: Abstract. Flexible display has been attracting attention in the research field of next generation display in recent years. And polymer is a candidate material for flexible displays as it takes advantages including transparency, light weight, flexibility and so on. Rolling process is suitable and competitive process for the high throughput of flexible substrate such as polymer. In this paper, we developed a prototype of roll-to-flat (R2F) thermal imprint system for large area micro pattern replication process, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…P2P based 8 inch wafers can take 20,000 N of imprint force [ 157 ], however, the R2P method only needs 200 N for a 300 mm width imprint. Flexible polymer film based R2P methods were also introduced as shown in Figure 8 b [ 158 , 159 ]. They used the thermal NIL mechanism with a heated mold and roller.…”
Section: Printing Methodsmentioning
confidence: 99%
“…P2P based 8 inch wafers can take 20,000 N of imprint force [ 157 ], however, the R2P method only needs 200 N for a 300 mm width imprint. Flexible polymer film based R2P methods were also introduced as shown in Figure 8 b [ 158 , 159 ]. They used the thermal NIL mechanism with a heated mold and roller.…”
Section: Printing Methodsmentioning
confidence: 99%
“…This concept or technique is also observed in the work of Kim and the group [ 6 ]. Additionally, the roller may also be used to press a flexible polymer film onto the mold for imprinting via thermal NIL as observed in the work of Song et al [ 36 ] and Lim et al [ 37 ], as shown in Figures 5 and 6 . As the polymer film is pressed onto the heated mold using a roller, it becomes softened (or molten stage), where it will fill in the mold cavities under the given pressure.…”
Section: Reviewmentioning
confidence: 99%
“…To overcome the issues, recent NIL development has tended to focus on roller-based NIL process, which is more advantageous as it requires low imprint force, yields higher throughput and better uniformity without the need for vacuum environment [13,15,16]. Its suitability for large area imprinting also observed the roller-based NIL processes being widely applied in industries for the fabrication of flexible electronics as seen in the work of Zang and Liang from SiPix Inc. [17], J-G. Kim [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the conventional NIL method using plate-to-plate (P2P) contact is not suitable for large area imprinting due to its high-force [12] and vacuum environment requirements [7,9], low throughput [13,14] and non-uniformity issues [15].…”
Section: Introductionmentioning
confidence: 99%